Novel polyorganosiloxane xerogels with bifunctional ≡Si(CH₂)₃H/≡Si(CH₂)₃NH₂ surface layer - Melnyk (Seredyuk), I.V.; Zub, Yu.L.; Chuiko, A.A.; Van Der Voort, P. (Поверхность, 2002)
Novel polyorganosiloxanes gels with bifunctional (≡Si(CH₂)₃H/≡Si(CH₂)₃NH₂) surface layer have been prepared by a sol-gel technique using silane-ternary systems. The surface properties of the obtained gels are highly reproducible. The effect of the addition of a catalyst was investigated, and it is shown that the addition of fluoride ion has a highly beneficial effect on the porous properties of the materials. The synthesized samples have specific surface areas up to 250 m²/g, and have a high potential as selective sorbents for heavy and noble metals (Hg²⁺, Ag⁺, Au³⁺ etc.).